2014
DOI: 10.3748/wjg.v20.i19.5760
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular therapy in patients with cirrhosis: Challenges and options

Abstract: Tuberculosis (TB) has been a human disease for centuries. Its frequency is increased manyfold in patients with liver cirrhosis. The gold standard of TB management is a 6-mo course of isoniazid, rifampicin, pyrazinamide and ethambutol. Although good results are seen with this treatment in general, the management of patients with underlying cirrhosis is a challenge. The underlying depressed immune response results in alterations in many diagnostic tests. The tests used for latent TB have many flaws in this group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 87 publications
0
34
0
Order By: Relevance
“…Hepatotoxicity is the major adverse effect of PZA and usually occurs in the first 2 months of treatment (2). Previously reported studies showed a high incidence of hepatotoxicity with a high dosage of 40 to 70 mg/kg of body weight and a low rate of liver injury with a daily dose of Ͻ35 mg/kg (3).…”
mentioning
confidence: 99%
“…Hepatotoxicity is the major adverse effect of PZA and usually occurs in the first 2 months of treatment (2). Previously reported studies showed a high incidence of hepatotoxicity with a high dosage of 40 to 70 mg/kg of body weight and a low rate of liver injury with a daily dose of Ͻ35 mg/kg (3).…”
mentioning
confidence: 99%
“…Third, the short-term administration of hepatoprotectants might be considered another limitation. Although the normal duration of anti-TB treatment is 6 months [23], the longest duration of hepatoprotectant use in the included studies was 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The major challenge in successful TB treatment is the management of cirrhosis and its associated immune problems [3]. Lymphocyte and macrophage dysfunction, and decreased production of interferon gamma and tumor necrosis factor alpha, have been associated with cirrhosis progression and increased risk of TB infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although TB mortality rates decreased by approximately 35 % between 1990 and 2009, because of advances in medical treatment, TB remains the major serious infectious disease in Taiwan [1]. Isoniazid (INH) and rifampicin (RIF), or their combination (INH + RIF), are the most commonly used anti-TB chemotherapeutic drugs [2,3]. However, the use of these compounds is associated with severe liver disease in developing countries [4].…”
Section: Introductionmentioning
confidence: 99%